Evolution and current development trends of the Russian Federation’s higher education system - Butakova, Marina M.; Sokolova, Olga N.; Zaitseva, Natalia A.; Larionova, Anna A.; Ignatova, Marina N.; Trufanova, Svetlana N.; Yakovlev, Alexander Y. (Opción, 2020)
The aim of the study is to substantiate evolutionary development stages and current trends in the higher education system in the Russian Federation via general scientific methods of cognition, quantitative and qualitative assessment, methods of comparative and factor analysis, analysis and synthesis, grouping and comparison, the method of logical generalization. As a result, increasing globalization changes the approach to education. The authors came to the conclusion that it is necessary to take into account the impact of external and inter systemic factors on the development of higher education organizations in the Russian Federation.